2013
DOI: 10.1080/15732479.2012.681790
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lifetime losses of low-rise reinforced concrete buildings attacked by corrosion and earthquakes using a novel method

Abstract: In the estimation of the losses caused by an earthquake for a reinforced concrete (RC) building, the effect of corrosion of the reinforcing steel incurred by environmental conditions, e.g. carbonation and chloride ions, is seldom mentioned because of the corrosion with uncertainty and time dependence. However, because the structural capacity of a corroded RC building declines over time, one must apply an appropriate method that estimates the structural capacity of an RC building in a corrosive environment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the evaluation of corroded concrete structures, data from inspection and monitoring can be obtained to provide a more reliable analysis of the condition of the structure. In this review, 23 of 94 articles (24,5%) present real data from structures [6], [8], [10], [19], [22], [34], [38], [43], [45]- [47], [55], [74], [78], [80], [92], [94]- [97], [106], [109], [111].…”
Section: Experimental and Monitoringmentioning
confidence: 99%
“…In the evaluation of corroded concrete structures, data from inspection and monitoring can be obtained to provide a more reliable analysis of the condition of the structure. In this review, 23 of 94 articles (24,5%) present real data from structures [6], [8], [10], [19], [22], [34], [38], [43], [45]- [47], [55], [74], [78], [80], [92], [94]- [97], [106], [109], [111].…”
Section: Experimental and Monitoringmentioning
confidence: 99%
“…They integrated the theory of structural safety degree and the concept of mathematical statistics and proposed a reliability analysis calculation model. Then earliest reliability calculation model was extensively recognized and studied by other scholars [9]. In 1969, Cornell, an American expert, proposed the concept of reliability index, integrated it with structural failure rate and put forward the conversion formula with regard to reliability index and structural failure rate [10].…”
Section: Development and Status Of Structural Reliability Analysis Mementioning
confidence: 99%
“…Analytical results showed that the effect of corrosion on seismic performance was highly significant, and it should be considered carefully in performance analysis. Chiu and Chi (2013) proposed mechanical models for corroded beam or column members and adopted a superposition method, which is not suggested by ATC-40 (1996), to simulate the structure performance of an RC building. Although the proposed method in that study is effective to evaluate lifetime losses of corroded RC buildings under seismic events, the mechanical models for corroded members should be verified by experimental data.…”
Section: Introductionmentioning
confidence: 99%